2020
DOI: 10.1021/acsestengg.0c00054
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Reactor Design for Electrocatalytic Nitrite Reduction with Minimal Mass Transfer Limitations

Abstract: A parallel-plate thin-layer (PPTL) flow reactor with potential control and custom-made cathode of Pd−In modified activated carbon cloth was developed for electrocatalytic removal of nitrite from water; the effect of applied potential and flow rate were investigated. Compared to other reactors in the literature, rapid nitrite reduction (first-order rate constant is 0.38 L g Pd −1 min −1 ), high current efficiency (CE, 51%), and low ammonium selectivity (5.4%) were observed at an applied potential of −0.60 V vs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 74 publications
(127 reference statements)
2
37
0
Order By: Relevance
“…Generally, transition metals exhibit higher selectivity toward NH 3 in acidic solutions due to high proton concentrations. 78 The precious metals (e.g., Pd, Pt, Ru, and Ir) have a high affinity toward hydrogen, which leads to the competitive adsorption between N-species and hydrogen. 48 It was reported that the hydrogen atoms occupy more active sites at more negative potentials, suppressing the adsorption of NO 3 − and N-intermediates and decreasing the NO 3 RR efficiency.…”
Section: The Reaction Pathways Of No 3 Rrmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, transition metals exhibit higher selectivity toward NH 3 in acidic solutions due to high proton concentrations. 78 The precious metals (e.g., Pd, Pt, Ru, and Ir) have a high affinity toward hydrogen, which leads to the competitive adsorption between N-species and hydrogen. 48 It was reported that the hydrogen atoms occupy more active sites at more negative potentials, suppressing the adsorption of NO 3 − and N-intermediates and decreasing the NO 3 RR efficiency.…”
Section: The Reaction Pathways Of No 3 Rrmentioning
confidence: 99%
“…An adsorbed NO can be reduced by five adsorbed hydrogen atoms consecutively to produce NH 3 (eqs –). Adsorbed hydrogen atoms on precious metals such as Pt and Pd facilitate the formation of N–H bonds in acidic solutions. , Generally, transition metals exhibit higher selectivity toward NH 3 in acidic solutions due to high proton concentrations . The precious metals (e.g., Pd, Pt, Ru, and Ir) have a high affinity toward hydrogen, which leads to the competitive adsorption between N-species and hydrogen .…”
Section: The Reaction Pathways Of No3rrmentioning
confidence: 99%
“…For electrocatalytic treatment, electricity costs required to generate hydrogen in situ were determined from our recent work assuming ∼50% hydrogen use efficiency for NO 3 − reduction to N 2 . 49 Pd costs were determined assuming reaction kinetics from a trickle bed reactor, and either a 20-, 5-, or 1-year Pd life span. Faster kinetics have been realized for electrocatalytic reactors, and these will be discussed in a subsequent section.…”
Section: ■ Costs For Ion Exchange and (Electro)catalytic Treatment An...mentioning
confidence: 99%
“…139 In the latter case, Yan et al showed that the production of molecular hydrogen can be eliminated when nitrite reduction is promoted above −0.61 vs Ag/AgCl reference electrode in a pH 6.5 electrolyte. 49 This approach favors complete hydrogen utilization because no off-gassing occurs, and it favors N 2 production by limiting hydrogen coverage on the catalyst surface.…”
Section: ■ Rate Limiting Nitrate Reduction Mechanisms Driving Platinu...mentioning
confidence: 99%
See 1 more Smart Citation